Conformational dynamics of a lipid-interacting protein: MD simulations of saposin B. - Stokeley, D; Bemporad, D; Gavaghan, D; Sansom, MS (2007)
Saposin B is a water soluble alpha-helical protein which can bind to membranes and extract selected lipids, especially cerebroside sulfates. The X-ray structure of saposin B is homodimeric. There are two conformations of the dimer in the crystal-one with a closed central cavity (the AB dimer) and one (the CD dimer) with a more open cavity. We have conducted a series of short (5 ns) molecular dynamics simulations of saposin B, starting from both the AB and CD conformations and with/without bound lipid and/or water molecules within the central hydrophobic cavity. The more open (CD) dimer showed greater conformational drift than the AB dimer. The conformational drift was also somewhat higher in the absence of bound lipid. Two more extended (30 ns) simulations of AB and CD dimers were performed and analyzed in terms of changes in intersubunit packing within the dimers. The AB dimer remained largely unchanged in conformation over the duration of the extended simulation. In contrast, the CD dimer underwent a substantial conformational change corresponding to a 'scissor' motion of the two monomers so as to compress the central cavity to a more closed conformation than that seen in the AB dimer structure. A H-bond between the Q53 and Y54 side chains of the alpha3 helices of the two opposing monomers seems to hold the dimer in this 'scissor-closed' conformation. We suggest that a cycle of conformational changes, expanding and compressing the central cavity of the saposin B dimer, may play a key role in facilitating lipid extraction from bilayers.